Pengaruh Work Life Balance Dan Pemberian Kompensasi Terhadap Kinerja Dengan Kepuasan Kerja Sebagai Intervening - Sarah Rahmiati Meha; Ramdani Bayu Putra; Susriyanti; Hasmaynelis Fitri (CV. ITTC INDONESIA, 2025)
This research aims to determine and analyze whether there is an influence from work-life balance and compensation on employee performance with job satisfaction as an intervention variable for PT Hayati Pratama Mandiri employees, Padang, West Sumatra. This research is a quantitative research with descriptive and explanatory research methods. The population in this study is employees of PT Hayati Pratama Mandiri, Padang, West Sumatra with a total of 54 employees with a research sample of 54 people. Data collection techniques in this research are questionnaires, interviews, and observations. This research model is structural equation modelings (SEM), with analysis tools using SmartPLS 3. The results obtained that work-life balance has a negative and insignificant effect on employee performance. Compensation has a negative and insignificant effect on employee performance. Work-life balance has a positive and significant effect on employee job satisfaction. Compensation has a negative and insignificant effect on employee job satisfaction. Job satisfaction has a negative and insignificant effect on employee performance. Work life balance indirectly through job satisfaction as an intervention variable has a negative and insignificant effect on employee performance. Indirect compensation through job satisfaction as an intervention variable has a negative and insignificant effect on employee performance.